VARIATIONS CLIMATIQUES ET PHÉNOLOGIE DES POACÉES DANS LA RÉGION DE CONSTANTINE (ALGÉRIE) - Boulacel Mouad; Benlaribi Mostefa (European Scientific Journal, ESJ, 2015)
The proposed study was carried out at the region of Constantine, northeast of Algeria. Therefore, we have recorded climatic variations linked to the increase and the decline of the temperature during two agricultural campaigns. The aim of this study was to establish a floral calendar of Poaceae encountered in the region and so to determine the effect of these variations on phenological stages and their consequences on yield. The obtained results showedthe presence of 28 plant species of the study family distributed according to the period of blooming in two groups. The comparison between campaigns revealed a delay of blooming of 6.3 days on average during the campaign of 2013/2014 which is explained by a decrease of the temperature of 2.5°C during the month of Marsh. This delay in the blooming causes negative effects resulting in a decrease of the yield.